Investigation of the electrical and optical properties of advanced semiconductors materials and devices - AL HUWAYZ, MARYAM (2022)
This thesis reports on an investigation of deep level defects in InAs quantum dots intermediate band solar cells (QD-IBSCs) and InAs/InGaAs quantum dot lasers structures that have applications in photovoltaics and optoelectronic technologies. In fact, it is of paramount importance to understand the characteristics of the defects and their influence on the quality of materials and the performance of devices. In this work, the effect of electrically active defects on the structural, optical and electrical properties of a set of intermediate band solar cells grown by Metal Organic Vapour Phase Epitaxy (MOVPE) and self-assembled InAs/InGaAs QDs based laser structures grown by Molecular Beam Epitaxy was studied using Atomic Force Microscopy, Transmission Electron Microscopy, Photoluminescence, current-voltage (I-V), capacitance-voltage (C-V), deep level transient spectroscopy (DLTS), and Laplace DLTS (LDLTS) techniques. In addition, the effect of Gamma irradiation on the properties of laser structures was also investigated.